2019
DOI: 10.1016/j.esxm.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Plaque Incision and Grafting for Peyronie’s Disease: A Review of Literature

Abstract: Introduction Plaque incision and grafting (PIG) is indicated for men with complex or severe penile curvature and, despite a multitude of incision types and grafting materials having been used, no individual technique has proven superiority. Aim To assess outcomes following PIG and to understand the operative technique. Methods A systematic review was performed to find all relevant studies reporting on use of the PIG technique to correct curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…When erectile dysfunction exists, penile prosthesis implantation is required, which is out of the scope of this article 2 . Reconstruction techniques are advised when the erectile function is satisfactory (with or without medication) 11 . These techniques include plication and grafting methods (first shortens the convex aspect, latter elongates the concave side).…”
Section: Discussionmentioning
confidence: 99%
“…When erectile dysfunction exists, penile prosthesis implantation is required, which is out of the scope of this article 2 . Reconstruction techniques are advised when the erectile function is satisfactory (with or without medication) 11 . These techniques include plication and grafting methods (first shortens the convex aspect, latter elongates the concave side).…”
Section: Discussionmentioning
confidence: 99%
“…22,35,70 No TA incision type has proven to be superior over others. 71 A variety of grafts are now available to the reconstructive surgeon, including autologous grafts, allografts, synthetic grafts and xenografts. The distribution of graft materials based on the reviewed evidence is summarized in…”
Section: Evidencementioning
confidence: 99%
“…Patient satisfaction rates, which take into account not only straightness, but also other aspects, such as postoperative penile length and erectile function, are similarly variable, ranging from 60 to 100% 35 . Postoperative complications that compromise patient satisfaction include perceived penile shortening (0–90%) and penile sensory changes (0–22%) 35,118,122 . Sensory changes are transient in the majority of patients, and a recent report from Terrier et al.…”
Section: Surgerymentioning
confidence: 99%
“…Sensory changes are transient in the majority of patients, and a recent report from Terrier et al. found that, although 20% of men experienced some degree of glans hypoesthesia at 1 month after grafting, just 3% had persistent deficits at 12 months postoperatively 122,123 . Subjective and objective penile length loss can also be allayed by postoperative penile rehabilitation with PTT or VT 17,124 …”
Section: Surgerymentioning
confidence: 99%